2005
DOI: 10.1002/adsc.200505018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Primary Amines to N‐Monoalkylhydroxylamines using Sodium Tungstate and Hydrogen Peroxide‐Urea Complex

Abstract: Abstract:The sodium tungstate-catalyzed (10 mol %) oxidation of primary amines with a urea-hydrogen peroxide complex (UHP) gives the corresponding N-monoalkylhydroxylamines, which are important biologically active compounds, in good to excellent yields. The method is applicable for a wide range of primary amines, including chiral benzylic amines, a-1,2-hydroxylamine and a-amino esters.Keywords: homogeneous catalysis; hydroxylamines; tungsten; urea-hydrogen peroxide complex a-Hydroxylamino acids and hydroxamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Oxidation of primary amines to oximes and N‐oxide can occur in non‐aqueous phase . However, this usually does not occur in aqueous solution because the primary amine is virtually non‐reactive chemically when it is protonated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of primary amines to oximes and N‐oxide can occur in non‐aqueous phase . However, this usually does not occur in aqueous solution because the primary amine is virtually non‐reactive chemically when it is protonated.…”
Section: Discussionmentioning
confidence: 99%
“…2 Oxidation of primary amines to oximes and N-oxide can occur in non-aqueous phase. 24 However, this usually does not occur in aqueous solution because the primary amine is virtually non-reactive chemically when it is protonated. Moreover, the products formed cannot be easily detectable because of its high instability in aqueous environments.…”
Section: Discussionmentioning
confidence: 99%
“…As part of our work on Cope-type hydroaminations over the past 15 years, we have surveyed many direct and indirect methods for the synthesis of complex N,N -dialkylhydroxylamines. ,, This work indicated that there is a clear need and opportunity for the development of direct oxidative methods to prepare 2° hydroxylamines from 2° amines. Herein, we report two sets of conditions for the synthesis of N , N -dialkylhydroxylamines from secondary amines and the urea hydrogen peroxide adduct (UHP) as the oxidant (Scheme C) . The first method (Method A) uses 5 equiv of amine in 2,2,2-trifluoroethanol (TFE) to prevent overoxidation.…”
Section: Introductionmentioning
confidence: 99%